Personality and Learning Effectiveness of Teams in Information Systems Education Courses - Shuto, Masashi; Washizaki, Hironori; Fukazawa, Yoshiaki; Yamato, Shoso; Okubo, Masashi; Tenbergen, Bastian (EAI Endorsed Transactions on e-Learning, 2018)
The goal of this paper is to clarify the optimal combination of team members to maximize the learning effectiveness in information systems education courses. We surveyed the correlation of students’ five factor model personalities and the learning effectiveness, which is the amount of increase in team management or technical knowledge, and skill, which is the IPA common carrier skill framework based on SFIA. Specifically, we targeted were three actual courses (a System Development Project course, an IT Management Project course, and an Application Development Project course) to elucidate the relationships between personality characteristics and learning effectiveness. Although individual students’ personality characteristics are not strongly related to learning effectiveness, team personality characteristics are related to learning effectiveness. In particular, Neuroticism and Conscientiousness characteristics are negatively correlated to learning effectiveness.